Classification of Injurious Fall Severity in Hospitalized Adults. (7th January 2020) - Burns, Zoe; Khasnabish, Srijesa; Hurley, Ann C; Lindros, Mary Ellen; Carroll, Diane L; Kurian, Susan; Alfieri, Lois; Ryan, Virginia; Adelman, Jason; Bogaisky, Michael; Adkison, Lesley; Ping Yu, Shao; et al.
Abstract: Background: Many hospital systems in the United States report injurious inpatient falls using the National Database of Nursing Quality Indicators categories: None, Minor, Moderate, Major, and Death. The Major category is imprecise, including injuries ranging from a wrist fracture to potentially fatal subdural hematoma. The purpose of this project was to refine the Major injury classification to derive a valid and reliable categorization of the types and severities of Major inpatient fall-related injuries. Methods: Based on published literature and ranking of injurious fall incident reports ( n = 85) from a large Academic Medical Center, we divided the National Database of Nursing Quality Indicators Major category into three subcategories: Major A—injuries that caused temporary functional impairment (eg, wrist fracture), major facial injury without internal injury (eg, nasal bone fracture), or disruption of a surgical wound; Major B—injuries that caused long-term functional impairment or had the potential risk of increased mortality (eg, multiple rib fractures); and Major C—injuries that had a well-established risk of mortality (eg, hip fracture). Based on the literature and expert opinion, our research team reached consensus on an administration manual to promote accurate classification of Major injuries into one of the three subcategories. Results: The team tested and validated each of the categories which resulted in excellent interrater reliability (kappa = .96). Of the Major injuries, the distribution of Major A, B, and C was 40.3%, 16.1%, and 43.6%, respectively. Conclusions: These subcategories enhance the National Database of Nursing Quality Indicators categorization. Using the administration manual, trained personnel can classify injurious fall severity with excellent reliability.